Major lineages of Nolidae (Lepidoptera, Noctuoidea) elucidated by molecular phylogenetics. (5th November 2012) - Zahiri, Reza; Lafontaine, J. Donald; Holloway, Jeremy D.; Kitching, Ian J.; Schmidt, B. Christian; Kaila, Lauri; Wahlberg, Niklas
Abstract: To elucidate the evolutionary relationships of the major lineages within the moth family Nolidae, we analysed a molecular dataset comprising eight independent gene regions (6.4 kbp), cytochrome c oxidase subunit I (COI) from the mitochondrial genome, and elongation factor‐1α (EF‐1α), ribosomal protein S5 (RpS5), carbamoylphosphate synthase domain protein (CAD), cytosolic malate dehydrogenase (MDH), glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH), isocitrate dehydrogenase (IDH) and wingless genes from the nuclear genome, using parsimony and model‐based evolutionary methods (maximum likelihood and Bayesian inference). Our analyses revealed a well‐resolved phylogenetic hypothesis, again recovering the six previously recognized families within Noctuoidea (i.e. Oenosandridae, Notodontidae, Euteliidae, Erebidae, Nolidae and Noctuidae), and monophyly of the quadrifid Noctuoidea (i.e. Euteliidae, Erebidae, Nolidae and Noctuidae). The family Nolidae is diagnosed and characterized by two synapomorphies from morphology: construction of a ridged boat‐shaped cocoon that bears a vertical exit slit at one end; and two other morphological character states: elongation of the forewing retinaculum into a bar‐like or digitate condition and possession of a postpiracular counter‐tympanal hood. We present a new phylogenetic hypothesis for Nolidae consisting of eight strongly supported subfamilies, two of which are erected here: Diphtherinae, Risobinae, Collomeninae subfam. nov., Beaninae subfam. nov., Eligminae, Westermanniinae, Nolinae and Chloephorinae. Where we are able, each monophyletic lineage is diagnosed by morphological autapomorphies and within each subfamily, monophyletic tribes and subtribes are circumscribed, most of which are also diagnosable by morphological apomorphies. We also describe two new taxa: Gelastocerini trib. nov. and Etannina subtrib. nov. The Neotropical subfamily Diphtherinae, here newly circumscribed, is considered to be the plesiomorphic sister lineage to the rest of Nolidae. Diphtherinae are characterized by loss of the proximal pair of metatibial spurs in males and by the presence of a frontal tubercle, which is presumably associated with a derived strategy of emergence from the cocoon.